Decision Making in the Digital Era: In Search of a Framework for the Use of Social Technology - Amaripuja, Punang; Tjahjono, Heru Kurnianto; Muafi, Muafi; Prajogo, Wisnu (Universitas Muhammadiyah Yogyakarta, 2022)
The unfortunate events occurring during the COVID-19 pandemic have forced many companies to promote work-from-home procedures and consequently have put forth the urgency to identify critical success factors and develop best practices for the use of social technologies. In the long run, these practices may turn out to be the main practice of doing business, rather than being an emergency response to external conditions. A better understanding of the relationships between social technology on decision-making is vital for an organization since the intensive use of social technology would require several changes in an organization’s culture and business process. For this reason, this paper offers a framework for understanding how the fit and viability of tasks, technology, and organization through the use of social technology effects decision-making performance. The framework suggests three propositions: 1) fit has a positive effect on social technology use, 2) viability has a positive effect on social technology use, and 3) social technology use has a positive effect on decision-making performance.